2000
DOI: 10.1007/bf03018973
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to anesthetic induction in patients chronically treated with angiotensin-converting enzyme inhibitors

Abstract: Purpose: To investigate the effects of chronic ACE inhibition on cardiac neural function following induction of general anesthesia in patients with underlying coronary artery disease. Method:In a prospective case-control study, heart rate variability (HRV) and baroreflex control were compared preoperatively and 30 min after anesthesia induction in patients receiving, or not, ACEI (n=16, control group and n=16, ACEI group). All patients had normal cardiac function and anesthesia consisted of a fixed dose regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 35 publications
(30 reference statements)
0
21
1
10
Order By: Relevance
“…In 1 report, intraoperative hypotension was associated with a greater incidence of perioperative cardiac and renal complications than intraoperative hypertension, although other studies have not shown this. 78,[91][92][93][94][95][96] Several authors have suggested withholding ACE inhibitors and angiotensin receptor antagonists the morning of surgery. [97][98][99] Consideration should be given to restarting ACE inhibitors in the postoperative period only after the patient is euvolemic, to decrease the risk of perioperative renal dysfunction.…”
Section: Hypertensionmentioning
confidence: 99%
“…In 1 report, intraoperative hypotension was associated with a greater incidence of perioperative cardiac and renal complications than intraoperative hypertension, although other studies have not shown this. 78,[91][92][93][94][95][96] Several authors have suggested withholding ACE inhibitors and angiotensin receptor antagonists the morning of surgery. [97][98][99] Consideration should be given to restarting ACE inhibitors in the postoperative period only after the patient is euvolemic, to decrease the risk of perioperative renal dysfunction.…”
Section: Hypertensionmentioning
confidence: 99%
“…32 Studies have shown that patients who are on long-term treatment, with ACE inhibitors and angiotensin receptor blockers, experience hypotension that requires vasopressor treatment more often after induction of anesthesia, than those in whom such medications have been withheld on the day of surgery. [33][34][35] Withdrawal of hypertensive medications during the preoperative period may result in rebound HTN that may require immediate treatment. Although the presence of labile BP during the perioperative period has been shown to increase the risk of stroke, acute kidney injury (AKI), and 30-day mortality in patients undergoing cardiac surgery, 36 evidence is limited in the ambulatory patient population.…”
Section: Hypertensionmentioning
confidence: 99%
“…Die Fortführung einer präoperativ bestehenden antihypertensiven Therapie zur Nachlastsenkung wird empfohlen, ist aber nicht durch große randomisierte Studien belegt. Bei perioperativer Einnahme von Angiotensinkonversionsenzym(ACE)-Hemmern und Angiotensin(AT)II-Rezeptor-Antagonisten sind perioperative Hypotonien und vasoplegische Syndrome beschrieben; der perioperative Umgang mit diesen Substanzklassen wird derzeit kontrovers diskutiert [28,29,30]. Liegt eine schwere AI mit progredienter linksventrikulärer Dysfunktion vor, wird ein Aortenklappenersatz vor elektiven nichtkardiochirurgischen Eingriffen empfohlen [10,31].…”
Section: Pathophysiologieunclassified